1991
DOI: 10.1152/jappl.1991.70.6.2691
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyperventilation on oxygenation of the brain cortex of newborn piglets

Abstract: A new phosphorescence imaging method (Rumsey et al. Science Wash. DC 241: 1649-1651, 1988) has been used to continuously monitor the PO2 in the blood of the cerebral cortex of newborn pigs. A window was prepared in the skull and the brain superfused with artificial cerebrospinal fluid. The phosphorescent probe for PO2, Pd-meso-tetra(4-carboxyphenyl)porphine, was injected directly into the systemic blood. The phosphorescence of the probe was imaged, and the lifetimes were measured using flash illumination and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
65
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(66 citation statements)
references
References 0 publications
0
65
1
Order By: Relevance
“…In addition, in the management of the premature infant "permissive hypercapnia" with mild respiratory acidosis has been anticipated to reduce the risk of periventricular leukomalacia (10,28). In contrast, accumulating evidence suggests the adverse neurologic consequences of hypocapnia, explained in part by cerebral vasoconstriction and increasing Hb O 2 affinity (21,29,30). In accordance with these findings, in the immature rat Vannucci and co-workers (31) have shown that hypercapnic (PaCO 2 ϭ 54 torr) cerebral hypoxia-ischemia was more neuroprotective than normocapnic hypoxia-ischemia, and hypocapnic hypoxia-ischemia was associated with more severe brain damage than that which is normocapnic.…”
mentioning
confidence: 99%
“…In addition, in the management of the premature infant "permissive hypercapnia" with mild respiratory acidosis has been anticipated to reduce the risk of periventricular leukomalacia (10,28). In contrast, accumulating evidence suggests the adverse neurologic consequences of hypocapnia, explained in part by cerebral vasoconstriction and increasing Hb O 2 affinity (21,29,30). In accordance with these findings, in the immature rat Vannucci and co-workers (31) have shown that hypercapnic (PaCO 2 ϭ 54 torr) cerebral hypoxia-ischemia was more neuroprotective than normocapnic hypoxia-ischemia, and hypocapnic hypoxia-ischemia was associated with more severe brain damage than that which is normocapnic.…”
mentioning
confidence: 99%
“…Wilson and coworkers (17)(18)(19) recently pioneered a phosphorescence technique and obtained macroscopic, twodimensional images (12,000 anm x 8000 pm) of Po2 in normal and tumor tissue of anesthetized animals. We have used this technique to obtain Po2 values in single microvessels and the interstitial Po2 distribution at known distances from blood vessels with higher spatial resolution (1wl5 pm).…”
mentioning
confidence: 99%
“…We report here a noninvasive microscopic approach based on a modified Algire chamber preparation in severe combined immunodeficient (SCID) mice (21) and oxygen-dependent phosphorescence quenching (17)(18)(19)43) to measure Po2 in the microvascular and interstitial space of a human tumor xenograft. Blood flow and Po2 were measured with and without anesthesia in animals breathing air or carbogen.…”
mentioning
confidence: 99%
“…Knowing that hypocapniamediated vasoconstriction is maintained in hypoxic-ischemic encephalopathy raises concerns that low PCO 2 may accentuate secondary brain injury, not only by reducing cerebral perfusion, but by reducing O 2 delivery, increasing neuronal energy demands and DNA fragmentation, and depleting neuronal energy stores [4][5][6][7]. Indeed newborn animal models demonstrate that hypocapnia reduces cerebral blood flow following asphyxia and is associated with greater brain injury than observed in either eucapnic or hypercapnic animals [8,9].…”
mentioning
confidence: 99%